RELATION BETWEEN EXTENSIVE EXTREME PRECIPITATION IN POLAND AND ATMOSPHERIC CIRCULATION - Nowosad, Jakub; Stach, Alfred (Quaestiones Geographicae, 2014)
The basic aim of this study was to find relations between the dates of occurrence and characteristics of extensive extreme daily (24-h) precipitation totals (EEDPTs) and pressure systems. The analysis was conducted on the basis of precipitation data from the multi-year period 1956-1980 and the Grosswetterlagen classification of circulation situations. EEDPTs were taken to embrace those cases of maximum annual daily precipitation totals that were registered on the same day at a minimum of 75 precipitation stations. In the years 1956-1980 there were 209 such events. The hypothesis about the effect of a circulation situation on the probability of occurrence of an EEDPT was verified in quantitative terms, the reference being both the entire multi-year period and the seasonal variation in the occurrence of precipitation of this type. Next, circulation situations were compared in terms of amount-related parameters of EEDPTs (mean precipitation, coefficient of variation), their spatial features (perimeter, area), and precipitation volume. The analyses performed show a statistically significant dependence between the atmospheric circulation and extensive extreme precipitation. It was demonstrated that there were circulation situations during which EEDPTs occurred much more often or much more rarely than over the entire multi-year period under study. Also identified was the connection of an atmospheric circulation with the mean amount, coefficient of variation and volume of extensive extreme precipitation.